Cryoballoon ablation versus antiarrhythmic drug therapy as initial treatment for persistent atrial fibrillation: the multicenter randomized CEPAF trial - Tianyou Ling; Yazhou Lin; Yangyang Bao; Lin Chen; Wei Xu; Baopeng Tang; Jing Xu; Jingquan Zhong; Wei Li; Zhongbao Ruan; Qi Lu; Suxia Guo; et al. (Europace, 2026)
Abstract Background and Aims Evidence supporting first-line cryoballoon ablation (CBA) in treatment-naive persistent atrial fibrillation (PersAF) is limited. Consequently, we compared CBA with guideline-directed antiarrhythmic drug (AAD) therapy in this advanced form of disease. Methods This multicenter, prospective, randomized, open-label trial assigned 320 symptomatic, treatment-naive patients with PersAF (1:1) to CBA or AAD therapy. The primary endpoint was the first documented atrial tachyarrhythmia recurrence lasting at least 30 seconds during days 91-365. Secondary endpoints included recurrence during days 1-90 and 1-365, time-to-first recurrence, quality of life, and safety. Results In the intention-to-treat population, recurrence during days 91-365 occurred in 30/160 (18.8%) patients assigned to CBA and 71/160 (44.4%) assigned to AAD therapy (absolute difference, -25.6 percentage points; 95% confidence interval, -35.4 to -15.8; P<0.001). Supportive time-to-event analysis favored CBA (hazard ratio for AAD vs. CBA, 2.29; 95% confidence interval, 1.48-3.56; log-rank P<0.001). In CBA vs AAD comparisons, overall recurrence during days 1-365 was 23.8% vs. 55.6%, and early recurrence was 11.2% vs. 28.1% (both P<0.001; respectively). Improvement in AFEQT score was greater with CBA (17.3 vs. 6.6 points; P<0.001); whereas SF-12 component scores did not differ significantly. Adverse events recorded on event forms were infrequent in both cohorts. Conclusion In selected treatment-naive patients with PersAF, first-line CBA reduced atrial tachyarrhythmia recurrence and improved disease-specific quality of life compared with AAD therapy.